A ambiência nos centros de atenção psicossocial iii do município de Campinas - Santos, Erick (2024)
With its first records dating back to 2003, the ambience occurs in CAPS III units, its emergence and incorporation in the field of Mental Health and Psychosocial Care stemmed from the Psychiatric Reform and the National Humanization Policy within the SUS. Although widely present and practiced today in health services in general, the concept of ambience in the context of the CAPS III lacks comprehensive studies that favour its understanding and operationalization. Thus, the present research had the primary objective of identifying and understanding the concept and practice of ambience among professionals and managers at CAPS III units in the city of Campinas. The specific objectives were: a) to understand the function, definition and operationalization of ambience from the perspective of the professionals and managers; b) to identify the relationship between professional units and the ambience- related practices carried out by different professionals working in CAPS III; c) to describe the potentialities and challenges of the ambience from the perspective of the professionals and managers. This is exploratory, descriptive research with a qualitative approach, with CAPS III units in the city of Campinas as the field of investigation. A total of five managers and nine higher education professionals distributed in five CAPS III units in Campinas participated in this research. Data was collected through a Participant Characterization Form, a Service Characterization Form, a Semi- Structured Interview Guide for Professionals, and a Semi-Structured Interview Guide for Managers. The data from the forms completed by the professionals and managers were subjected to a simple descriptive analysis, while the interviews with higher education professionals underwent Thematic Analysis, generating the following thematic categories: Unveiling within the walls of CAPS III: Ambience, what is it and what is it for?; The art of caring in the ambience: balance between coexistence and therapeutic intervention; Perspectives and practices of the various centres of knowledge and professional training for the development of the ambience: the multidisciplinary exercise of sharing readings; Paths to the ambience: strengths and challenges; On the actors involved: management. In short, the research contributes significantly to the understanding of the ambience in CAPS III, deepening the theoretical framework regarding ambience in Psychosocial Care, as well as providing new knowledge that enhances the practical approaches of professionals who work or intend to work in CAPS. It highlights their crucial role in promoting care and Mental Health. It also added a new perspective by integrating the conceptualization and definition of ambience, and it pointed out the importance of promoting training programs and the need for participatory management as central aspects that can guide future improvements and innovations in practice. Additionally, this study highlighted the need for investment in CAPS III environments, whether at a scientific, macropolitical, or practical level, as this aspect proved to be essential for enhancing the quality of care provided in CAPS III services, as well as advancing care strategies within the field of Psychosocial Care.